Engagement in the foreign language classroom: Micro and macro perspectives. (November 2022) - Sulis, Giulia
Abstract: While second language (L2) engagement has gained increasing attention in recent years, most empirical research to date has examined this construct in the context of single tasks and under laboratory conditions. Given the ecologically situated and dynamic nature of engagement, there has been a growing call for research investigating this construct beyond isolated tasks and in authentic language classrooms (Hiver, Mercer, & Al-Hoorie, 2021). To fill this gap, this study examines fluctuations in behavioural, cognitive, and emotional engagement within and across four intact face-to-face L2 lessons spread across one academic year. A stimulated recall design was developed where 26 students from three French classes and two Spanish classes at a British university noted their levels of engagement on a chart at 2.5 min-intervals while watching the video replay of each lesson. This procedure was followed by semi-structured interviews in which learners commented on variations in engagement during the lesson. Findings revealed how engagement can be understood as an ongoing, dynamic process unfolding over multiple timescales. They have also shown that engagement can pursue different trajectories depending on the level of analysis and granularity chosen to examine the construct.